Implementación de un sistema de adquisición y visualización de los parámetros eléctricos en el módulo Motor-Generador de corriente continua en el laboratorio de máquinas eléctricas de la Universidad Técnica de Cotopaxi. - Ocampo Taco, Christian Oswaldo (2020)
This technological proposal focused on the implementation of a system that allows acquiring and visualizing in real time the electrical parameters of the DC motor-generator module of the laboratories of the Technical University of Cotopaxi. The system is comprised of current power transformers (TP and TC), an electronic board, an arduino MEGA card, clamp meters, voltage transformers, a rapsberry card and a Touch screen, which allow data acquisition to measure the electrical voltage variables and alternating and direct current (AC and DC). For this, the graphic method for non-sinusoidal waves was applied. It consisted of dividing the X axis with respect to the Y axis into a finite number of samples. Through this process the amplitude and the offset angle with respect to the origin of the wave were obtained in order to obtain the necessary coefficients an and bn to calculate the RMS values of voltage and current. The Arduino programming platform was used to acquire the electrical variables, and the signal processing and the visualization of the parameters in the stages (Module, Three-phase motor and Generator DC) were carried out through Python software. As a final result, the behavior of the waves and the electrical variables of the module could be evidenced, obtaining similarities in the calculation results and measurements made, which resulted in a relatively low error rate for the proposal validation